Introduction of AGPAT3 gene as a regulator of cisplatin resistance in A2780 ovarian endometrioid carcinoma cell line. - Hadi Alizadeh; Sana Kerachian; Sadegh Babashah; Bahram M Soltani (PLoS ONE)
Ovarian cancer therapy remains a challenge for human health, partly due to chemotherapy resistance. Understanding the molecular mechanisms underlying this resistance is crucial. Therefore, to identify genes involved in cisplatin resistance in ovarian cancer, RNA-seq analysis of A2780cp (cisplatin-resistant) and A2780 (cisplatin-sensitive) cell lines was performed, revealing 1-acylglycerol-3-phosphate O-acyltransferase 3 (AGPAT3) as a differentially expressed candidate gene. First, MTT analysis confirmed the drug resistance of A2780cp and the sensitivity of A2780 cell lines. Subsequent reverse transcription quantitative polymerase chain reaction (RT-qPCR) and western blotting analyses revealed elevated AGPAT3 and mTOR expression in A2780cp cells compared with A2780 cells. Additionally, western blotting showed increased p-mTOR (phospho-mTOR)/mTOR and p-S6K (phospho-S6K)/S6K ratios in A2780cp cells. The overexpression of AGPAT3 in A2780 cells led to increased p-mTOR/mTOR and p-S6K/S6K ratios and increased IC50 values, as shown by RT-qPCR, western blotting, and MTT analysis. Conversely, shRNA-mediated downregulation of AGPAT3 resulted in reduced p-mTOR/mTOR and p-S6K/S6K ratios. At the cellular level, AGPAT3 overexpression in A2780 cells increased survival rates, decreased apoptosis, and caused G2/M cell cycle arrest under cisplatin treatment, as detected by apoptosis assay, and cell cycle flow cytometry analysis. Overall, we conclude that AGPAT3 is involved in cisplatin resistance in A2780cp cells and propose that targeting this gene or its enzymatic product could help overcome drug resistance.